(untitled) (Research, Society and Development, 2022)
The aim of this study was to highlight the advantages and contributions brought by the point of care exams, pointing out the current consensus on this topic. A literature review was carried out, elaborated through data collection from secondary sources, through a bibliographic survey. The search for primary documents was carried out through the Scielo database, the Virtual Health Library (VHL) and PubMed. As inclusion criteria, the period from 2011 to 2021 was delimited, accepting full publications or only their published abstracts. Only articles published in Portuguese and English were accepted. The following descriptors were used: point of care, technology, diagnosis. Through the bibliographical survey carried out, it was possible to conclude that the point of care technology is extremely important, even essential for determining the definitive and confirmatory diagnosis of a series of pathological and clinical conditions in the daily routine of hospital care, especially. This technology should be increasingly encouraged in practice, considering not only the fact that it allows for an early diagnosis, but also because it provides a better prognosis for those cases considered more serious, contributing to the saving of lives.